2020
DOI: 10.4081/idr.2020.8716
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Touch DNA Analysis in Forensic Identification Focusing on Short Tandem Repeat-Combined DNA Index System Loci THO1, CSF1PO and TPOX

Abstract: Forensic identification through DNA analysis is an accurate diagnostic tool. Deoxyribonucleic Acid (DNA) analysis is via DNA repetitive regions with less than 1 kb base size is called ‘microsatellite’ or Short Tandem Repeat (STR). At the crime scene, the perpetrator’s skin may accidentally be in contact with surrounding objects, thereby transferring trace evidence to the objects. In this study DNA was obtained using “touch DNA” from two buccal smears and two smear from watches and cellphones from volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies continue to elucidate the ability to generate DNA profiles from samples taken from touched objects [61][62][63][64]. Additional studies evaluated means of generating human DNA profiles from traces of biological material left on various items, includ-ing hair [65], bricks [66], dogs [67], bite marks in food [68], paper documents [69], eye wear [70], superabsorbent polymer-containing products (commonly found in nappies and sanitary towels) [71], improvised explosive devices [72], rifle magazines [73] and bullet cartridges [74][75][76][77][78].…”
Section: Samplingmentioning
confidence: 99%
“…Several studies continue to elucidate the ability to generate DNA profiles from samples taken from touched objects [61][62][63][64]. Additional studies evaluated means of generating human DNA profiles from traces of biological material left on various items, includ-ing hair [65], bricks [66], dogs [67], bite marks in food [68], paper documents [69], eye wear [70], superabsorbent polymer-containing products (commonly found in nappies and sanitary towels) [71], improvised explosive devices [72], rifle magazines [73] and bullet cartridges [74][75][76][77][78].…”
Section: Samplingmentioning
confidence: 99%
“…The Federal Bureau of Investigation (FBI) and the world's forensic expert community designed 13 locus as a national forensic identification system that synergizes with the Combined DNA Index System (CODIS) database. For personal identification, the researcher chose the TPOX and TH01 locus because several studies have shown that the TPOX and TH01 locus have strong discriminating power in Asian populations 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The succession of natural catastrophic events (tsunamis and hurricanes), of terrorist attacks (11 September 2001 in New York, 11 March 2003 in Madrid and London, 13 November 2015 in Paris), air accidents and events related to the increasing frequency of use of industrial and military artifices, have determined the most urgent need to activate particular procedures aimed at solving problems of a medico-legal and pathological forensic nature [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. One of the most commonly accepted definitions is that a mass disaster is a situation that involves criticality between the number of victims and resources, in terms of both men and means, present on the site of the event which is mostly unexpected and sudden [ 13 ].…”
Section: Introductionmentioning
confidence: 99%